Do contextual factors matter? Evidence from Chinese hotel productivity with heterogeneity. Issue 2 (March 2020) - Dong, Hai; Peypoch, Nicolas; Zhang, Linjia
In this article, an assessment of efficiency and productivity of Chinese hotels at the provincial level in relation to their star rating is proposed. This heterogeneity is considered by using a hierarchical structure. The drivers of productivity and its components are studied through various and innovative environmental and contextual factors. This study shows that Chinese star-rated hotels experienced a slight productivity deterioration in the last decade. Furthermore, several contextual and environmental factors explain significant differences in productivity rankings of the Chinese provinces. These findings reveal important patterns that are useful for both hotel managers and policymakers.